MicroRNAs Enhance Keratinocyte Proliferative Capacity in a Stem Cell-Enriched Epithelium - Park, Jong Kook (PLoS One, 2015)
MicroRNAs are critical regulators of stem cell behavior. The miR-103/107 family is preferentially expressed in the stem cell-enriched corneal limbal epithelium and plays an important role in coordinating several intrinsic characteristics of limbal epithelial stem cells. To elucidate further the mechanisms by which miRs-103/107 function in regulating limbal epithelial stem cells, we investigate the global effects of miRs-103/107 on gene expression in an unbiased manner. Using antagomirs-103/107, we knocked down endogenous miRs-103/107 in keratinocytes and conducted an mRNA profiling study. We show that miRs-103/107 target mitogen-activated protein kinase kinase kinase 7 (MAP3K7) and thereby negatively regulate the p38/AP-1 pathway, which directs epithelial cells towards a differentiated state. Pharmacological inhibition of p38 increases holoclone colony formation, a measure of proliferative capacity. This suggests that the negative regulation of p38 by miRs-103/107 contributes to enhanced proliferative capacity, which is a hallmark of stem cells. Since miRs-103/107 also promote increased holoclone colony formation by regulating JNK activation through non-canonical Wnt signaling, we believe that this microRNA family preserves “stemness” by mediating the crosstalk between the Wnt/JNK and MAP3K7/p38/AP-1 pathways.